Spatial variability of life-history parameters of the Atlantic chub mackerel (Scomber colias), an expanding species in the northeast Atlantic - Domínguez-Petit, Rosario; Navarro, María Rosario; Cousido-Rocha, Marta; Tornero, Jorge; Ramos, Fernando; Hernández, Carmen; Landa, Jorge; Jurado-Ruzafa, Alba; Nunes, Cristina; Silva, Andreia V. (Scientia Marina, 2022)
Atlantic chub mackerel is a pelagic species present in the Atlantic Ocean that in recent decades has expanded northwards in the eastern Atlantic. Fish samples were collected in scientific surveys and commercial catches between 2011 and 2019. We analysed the geographical variation of the biological parameters (age, length, weight and condition), as well as the length-weight relationship, maturity-at-length and spawning season onset and duration in five geographical areas (from south to north): the Canary Islands, Gulf of Cadiz, western Portuguese coast, northwestern Spanish coast and Canta-brian Sea. The influence of sea surface temperature (SST) on fish length was modelled as a potential driver of geographical variability. All biological parameters increased progressively northwards, while the spawning season was delayed and prolonged with increasing latitude, from January in the Canary Islands to May-August in the Cantabrian Sea, when SST was between 15°C and 19°C. SST had a positive effect on length in three study areas and a negative one in two of them, suggesting that each group is at a different position within their thermal tolerance range. Deviance from the geographical pattern of some biological parameters in the Gulf of Cadiz suggests that it could be a hinge or mixing zone between Atlantic African, Mediterranean and Atlantic Iberian population components. Peer reviewed